Complete Tracheal Transection Following Blunt Trauma: A Case Report and Review of Literature - Yahaya, Ahmad Ibrahim; Radzi, Mohd (IIUM Medical Journal Malaysia, 2019)
Traumatic tracheobronchial injury is rare, but can be life-threatening. It is often associated with other fatal injuries. Early diagnosis and prompt treatment are crucial to produce the best outcome. We are reporting a 40-year-old gentleman, a lorry driver who had a head on collision with a car. He was brought to the casualty with an intact airway. ATLS was initiated and lead by trauma team. Subsequently in casualty, his conscious level dropped and he became distressed, hence a standard orotracheal intubation was performed. Following intubation, he developed massive subcutaneous emphysema to the neck and upper chest. Computed tomography (CT) showed tracheal injury at C7- T2 level, extensive subcutaneous emphysema, pneumomediastinum with malposition of the endotracheal tube. Emergency neck exploration was performed in operating theatre, and revealed a complete transection of trachea at the level of 2nd and 3rd tracheal ring. No other vital structures were injured. A tracheostomy was created, and the patient was managed in ICU for one day. Four days following the first surgery, he was transferred to a more specialized center for tracheal refashioning and anastomosis. The patient was discharged home later without a tracheostomy. In tracheobronchial injury, high level of suspicion based on clinical judgement is vital for prompt diagnosis, with adjunct of radiological investigation. Surgical intervention to establish a patent airway in operating theatre is undoubtedly crucial in a complete tracheal transection to prevent secondary insult from tissue hypoxia. In managing such injury, advance preparation should include setups for bronchoscopy and thoracotomy. Patient survival depends on preparation and prompt surgical intervention. A tailored surgical approach is often necessary for definitive repair.